Effects of probiotic supplementation on selected parameters of blood prooxidant-antioxidant balance in elite athletes: A double-blind randomized placebo-controlled study - Michalickova, D.; Kotur-Stevuljevic, J.; Miljkovic, M.; Dikic, N.; Kostic-Vucicevic, M.; Andjelkovic, M.; Koricanac, V.; Djordjevic, B. (Journal of Human Kinetics, 2018)
A randomized, double-blind, placebo-controlled study was conducted, in order to evaluate if Lactobacillus helveticus Lafti® L10 (Lallemand Health Solutions, Montreal, Canada) supplementation during three months could influence oxidative markers in the population of elite athletes: triathletes, cyclists and endurance athletes. Twenty-two elite athletes were randomized to either placebo (n = 12) or probiotic (n = 10) groups. The probiotic group received 2x1010 colony forming units of Lafti® L10. Before and after the supplementation serum samples were collected. Markers of oxidative stress and anti-oxidative defense: superoxide dismutase (SOD), paraoxonase (PON), advanced oxidation protein products (AOPP), malondialdehyde (MDA), total antioxidant status, total oxidant status, pro-oxidant-antioxidant balance, oxidative stress index, bilirubin, uric acid and albumin were determined in serum. Parameters of lipid status, as well as susceptibility to copper-induced oxidation of LDL particles in vitro were also determined. There was a significant interaction effect for MDA (p = 0.039), with a decrease in MDA in the probiotic group only (p = 0.049). There was a significant interaction effect for AOPP (p = 0.037), with a significant decrease in the probiotic group (p = 0.045). Interaction effect for SOD was approaching to formal significance (p = 0.108) and the post-hoc test showed a significant decrease in the probiotic group (p = 0.041) only. A significant correlation between AOPP and SOD (p = 0.012, r = -0.40) was found in the probiotic group at the end of the study. PON1 activity was decreased in both the probiotic (p = 0.032) and placebo group (p = 0.035). No significant changes in the remainder of the evaluated parameters were noted. In conclusion, probiotic strain Lafti® L10 exerts certain antioxidant potential, but further research is needed.